2002
DOI: 10.1039/b208407d
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of aryl-organochlorine compounds by catalytic reduction in supercritical carbon dioxide

Abstract: Pentachlorophenol, octachloronaphthalene and decachlorobiphenyl were smoothly converted to cyclohexanol, decalin and dicyclohexyl, respectively, by reaction, during 0.5-2 h, with excess hydrogen over alumina-supported palladium (5% w/w) in the presence/absence of supercritical carbon dioxide (50-90 °C). With these conditions, dechlorinations and dearomatization to their cyclic analogs were complete but no carbon-carbon bond scission was observed and only traces of partial deoxygenation/dimerization of the pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Thus, the presence of added CO 2 had no perceptible influence on the rate/course of the hydrogenation. In previous studies of the hydrodechlorination (HDC) of pentachlorophenol with this catalyst, it had been observed that rates of overall reaction, HDC plus dearomatization, were reduced somewhat by the presence of supercritical carbon dioxide [35]. It is considered that the active surface sites for hydrodechlorination and for hydrogenation/dearomatization are different.…”
Section: Hydrogenation Of Phenanthrene In Admixture With Carbon Dioximentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, the presence of added CO 2 had no perceptible influence on the rate/course of the hydrogenation. In previous studies of the hydrodechlorination (HDC) of pentachlorophenol with this catalyst, it had been observed that rates of overall reaction, HDC plus dearomatization, were reduced somewhat by the presence of supercritical carbon dioxide [35]. It is considered that the active surface sites for hydrodechlorination and for hydrogenation/dearomatization are different.…”
Section: Hydrogenation Of Phenanthrene In Admixture With Carbon Dioximentioning
confidence: 97%
“…Despite the fact that PAHs can be biodegraded, their persistence in soil, as measured in terms of half-life, can exceed eight years [33]. Our previous research [34,35] on catalytic hydrodechlorination of pentachlorophenol (PCP), octachloronaphthalene, decachlorobiphenyl and subsequent reduction of phenol, naphthalene or biphenyl by hydrogenation over selected transition metals had demonstrated that palladium on gamma-alumina was the most active of the catalysts evaluated.…”
Section: Supercritical Co 2 As a Reaction Mediummentioning
confidence: 97%
See 1 more Smart Citation
“…The hexane back‐extract could have been detoxified by catalytic hydrodechlorination over palladium sorbed to alumina. In this technique, the hexane is merged with a H 2 –supercritical CO 2 mixture and transported to a heated reactor (Yuan et al, 2003). The reactor effluent containing bicyclohexyl is judged to be toxicologically innocuous relative to the influent PCBs.…”
Section: Discussionmentioning
confidence: 99%
“…A broad array of techniques has been proposed to accelerate hydrodechlorination that includes electrochemical, 15 photochemical, 16 ultrasonic, 17 microbial, 18 radiolytic/ thermal 19 and chemical methods. 20,21 . In general, chemical methods remain the more widely exploited methods to accomplish the dechlorination of organochlorine (OC) compounds.…”
Section: Introductionmentioning
confidence: 99%